Refined Translation Methods for Culinary Recipes in the Book ‘Cooking with Love Ala Dapur Momychaa’- From Indonesian to English - Amanah, Firma Pradesta; Ariqah, Qatrunnada Virni (Yayasan Kyadiren, 2023)
Language and culture are inseparable in translation, as it facilitates knowledge exchange between diverse cultures. This study investigates translation techniques for recipes in “Cooking with Love ala Dapur Momychaa.” Using a qualitative approach, it explores semantic, literal, and word-for-word translation methods. The aim is to preserve the source text's meaning while ensuring understanding for readers of the translated version. The findings demonstrate successful translations, striving to maintain the original meaning while incorporating cultural nuances. Techniques like adaptation, literalism, amplification, calque, and description are employed. Encouraging more translators to undertake Indonesian recipe translations, this study promotes Indonesian cuisine and culture to foreign audiences fascinated by its culinary treasures.